Development of Business Strategies for Enhancing Competitiveness of Somfy Korea (aSSIST Business Review, 2026)
The motorized shading market is undergoing rapid changes driven by the advancement of smart home technologies and the spread of sustainable consumption trends. This study was conducted to analyze the growth potential and challenges of the motorized shading market from a management perspective and to contribute to future corporate strategy development, focusing on Somfy Korea. The research analyzes the growth drivers of the domestic motorized shading market, competitive landscape, and changes in consumer behavior to derive strategic recommendations. Key findings indicate that the motorized shading market continues to grow steadily, accounting for approximately 12% of the total indoor shading market as of 2020, driven by rising demand for smart home technology, energy efficiency, and premium interior design. Consumer behavior is shifting toward preferences for smart device integration, eco-friendly materials, and personalized products. The study recommends strategies focusing on smart home technology integration, customized product development, omni-channel marketing, and ESG-based sustainable product development to enhance Somfy Korea’s competitiveness.
Keywords: Motorized Shading; Smart Home; Somfy Korea; ESG; Competitive Strategy; Consumer Behavior